Implementasi Aplikasi Absensi Karyawan CV.Expressa dengan Pelacakan Lokasi dan Foto Pada Aplikasi - Susanto, Edy; Iskandar, Dwi; Pradana, Muhammad Yoga (Politeknik Indonusa Surakarta, 2023)
CV Expressa faces challenges with an attendance system that fails to provide adequate real-time monitoring of employee attendance and encounters difficulties in verifying the authenticity of attendance data. This has resulted in inefficiencies and unreliability in employee attendance management.This research employs data collection methods through observation, interviews, and literature review. The system development methodology applied is the Waterfall method, involving stages of requirement analysis, system design, implementation using the Flutter framework, testing, and maintenance. The database utilized is PostgreSQL.The CV Expressa employee attendance application features various functionalities in streamlining the attendance process and managing employee data. These include location tracking and capturing photos during attendance, providing strong authentication evidence. Moreover, the application offers convenience in maintaining a daily journal to record employee activities. The generated outputs encompass attendance reports, offering information on employee attendance, as well as salary reports for each employee.